The Role of Subjective Well-Being Mediation in the Test of the Influence of Teaching Competence on the Organizational Citizenship Behavior of Private Junior High School Teachers - Abdul Wahib (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This research aims to examine the influence of teacher competence on organizational citizenship behavior with the variable subjective well-being as an intervening variable in the hope of contributing to improving the quality of Private Tsanawiah Madrasas, especially in Lumajang Regency. This research is quantitative research with an explanatory research approach (Patel & Patel, 2019), research that explains the causal relationship between research variables through hypothesis testing. Data was obtained from filling out a questionnaire with 101 certified teacher respondents. The research results show that: 1) Teacher work competency does not affect teacher organizational citizenship behavior. 2) teacher work competence has a unidirectional effect on teachers' subjective well-being by 78.9%. 3) Teacher subjective well-being has a unidirectional effect on teachers' organizational citizenship behavior by 61.7%. 4) teacher work competence has a unidirectional effect on organizational citizenship behavior through subjective well-being variables being 48.7%